2007 IEEE International Conference on Bioinformatics and Biomedicine (BIBM 2007) 2007
DOI: 10.1109/bibm.2007.18
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Temporal Sequences in Chewing Sounds

Abstract: Abstract-Chewing is an essential part of food intake. The analysis and detection of food patterns is an important component of an automatic dietary monitoring system. However chewing is a time-variable process depending on food properties. We present an automated methodology to extract sub-sequences of similar chews from chewing sound recordings. The approach is based on a chew-accurate segmentation of the sound signal, a multi-objective evolutionary search for temporal partitions in the sequence using NSGA-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This observation was later confirmed using an automatic unsupervised sequence searching technique to group chewing strokes [19]. In contrast, the current work aims to establish the viability of a reduced occlusion sensor prototype.…”
Section: Acoustic Food Intake Monitoringmentioning
confidence: 69%
“…This observation was later confirmed using an automatic unsupervised sequence searching technique to group chewing strokes [19]. In contrast, the current work aims to establish the viability of a reduced occlusion sensor prototype.…”
Section: Acoustic Food Intake Monitoringmentioning
confidence: 69%
“…This effect was attributed to the low signal to noise ratio of these sounds. Moreover, the chewing sequence is not consistent over the entire intake cycle as assumed in the current approach [42]. This is observed as a variability in the detection confidences and hinders fusion methods such as LR to achieve a higher performance.…”
Section: Chewing Recognitionmentioning
confidence: 91%
“…In addition, they found that chewing sound patterns changed during the breakdown process of several chewing cycles. This observation was later confirmed using an automatic unsupervised sequence searching technique to group chewing strokes [3]. Lopez-Meyer et al used microphones to record chewing and swallowing sounds and detect periods of food intake by evaluation of the instantaneous swallowing frequency [17].…”
Section: Related Workmentioning
confidence: 93%